ANALISIS KESIAPAN UMKM BATIK DI KOTA MADIUN DALAM PENERAPAN SAK EMKM - Diza Satrina Luchindawati; Elva Nuraina; Elly Astuti (KRISNA: Kumpulan Riset Akuntansi, 2021)
MSMEs are small-scale business activities that can be controlled by groups or groups of people who aim to make a profit. UMKM is one of the pillars of a country's economy. However, the development of MSMEs from year to year is less significant. That condition happens because of a lack of knowledge about business financial management. The office in charge of MSMEs in several regions has begun to aggressively introduce financial reports preparation as information for the decision-making process. This socialization generally uses the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) as the legal basis for preparing their financial statements. This study aims to determine the readiness of batik micro, small and medium enterprises (MSMEs) in Madiun City to apply SAK EMKM to their business financial reports. This research uses descriptive qualitative method. This study indicates that batik UMKM players in Madiun City are not ready to implement SAK EMKM.